Neonatal Kawasaki syndrome presenting as out of hospital cardiac arrest rescued by extracorporeal cardiopulmonary resuscitation. (January 2020) - Tyson, Marguerite; Mustafa, Ala; Venugopal, Prem; Whitehead, Ben; Anderson, Ben; Mattke, Adrian Christian
A 7-week-old girl presented in severe shock to a local emergency department. During transfer to the quaternary pediatric hospital, the child had a cardiac arrest and cardiopulmonary resuscitation was commenced en route. Upon arrival to the pediatric intensive care unit, extracorporeal life support was initiated via trans-sternal cannulation. Chest CT performed after extracorporeal life support cannulation, demonstrated widespread aneurysms and a diagnosis of Kawasaki disease was made. Immunomodulatory therapy with immunoglobulin and glucocorticoid medication was commenced and the child was separated from extracorporeal life support after 48 hours. Our case highlights both an unusual presentation of Kawasaki disease and the role extracorporeal cardiopulmonary resuscitation can play in the treatment of this disease. It describes the youngest reported patient in the literature with Kawasaki disease rescued by extracorporeal cardiopulmonary resuscitation and highlights how extracorporeal life support therapy can facilitate appropriate investigations to resolve diagnostic uncertainty and treat the underlying condition.